Magnetic Nano-Fe3O4 Supported Ionic Liquids: A Recoverable Phase Transfer Catalyst for C-N Cross Coupling Reaction - Tang, Lin; Sun, Yu; Zhou, Lingyun; Shao, Taili (Asian Journal of Chemistry, 2013)
Magnetic nanoparticles-supported quaternary ammonium salts were prepared and evaluated as phase transfer catalysts. Some of them exhibited good activities in CuCl-catalyzed N-arylation of aryl amines and N-heterocycles with aryl iodides in aqueous solution without any ligands. They could be readily separated from reaction solution using an external magnet and reused three times with a little loss in activity.